Index of pseudo-projectively-symmetric semi-Riemannian manifolds - Gupta, P. (Carpathian Mathematical Publications, 2015)
The index of abla-pseudo-projectively symmetric and in particular for abla-projectively symmetric semi-Riemannian manifolds, where abla is Ricci symmetric metric connection, are discussed.